Test anxiety and achievement in mathematics of higher secondary students in Bengali Medium Schools - Ahmed Golam Yasdani; Kazi Masud Hossain; Patra, Anujit (Papanda Publisher, 2024)
This study intended to look at the connection between students' achievement in mathematics and their test anxiety at higher secondary level. Data were collected from 205 students in six schools located in Gazole Block, Malda district, West Bengal, using a descriptive survey method. For selected participants, a multistage method of sampling was employed. Data were gathered using the Anxiety Test Scale for Students, developed and standardized by Asamoah (2018) guaranteeing validity and reliability. For data analysis, the mean, t-test, and Pearson correlation coefficient techniques were applied. The results showed that there were notable differences in test anxiety between urban and rural students, as well as between male and female at the higher secondary level. However, there was no discernible difference in math proficiency between males and females or between rural and urban students. A negative correlation was observed between test anxiety and achievement in mathematics, suggesting that higher levels of test anxiety correspond to lower mathematics achievement scores. Conversely, addressing test anxiety among higher secondary students may contribute to enhance their performance in mathematics.